Comparative-General Classification of Medical Terms in French and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article attempts to conduct a systematic analysis of medical terminology, as well as a broader study of the structural and semantic features of the lexical semantic classification of medical terms in French and Uzbek.